Digital Writing Assessment through Padlet for grade XII IPA 4 students in SMA 4 Batam - Oinuma, Sachi; Lailliyah, Syafi’atul; Zaki, Leil Badrah (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2024)
This article delves into the transformative impact of digital writing assessment on the academic landscape, specifically targeting Grade 12 IPA students at SMA 4 Batam. In doing so, the subject was text caption writing as well as to find out their perceptions of using Padlet for learning text caption writing. It consisted of 42 students who were in grade 12. In an era dominated by technology, integrating digital tools in education has become imperative. Our study focuses on the efficiacy and adaptability of digital writing assessments to enhance the writing skills of high school students. We explore the multifaceted dimensions of digital assessment tools, examining their ability to provide timely feedback, foster collaborative learning environments, and cater to diverse learning styles. The research methodology involves a comprehensive analysis of student performance data, teacher perspectives, and the overall impact on the quality of written expression. Furthermore, we aim to provide valuable insights for eg,,,ducators, administrators, and policymakers seeking innovative approaches to elevate writing proficiency in the digital age. Based on the pre- and post-questionnaires and interviews conducted, our study aims to address the following research questions: How do students interpret and interact with various digital writing evaluation components How are digital writing evaluations implemented differently and what are the consequences on various linguistic backgrounds, ability levels, and demographic groups? What kind of professional development and technology assistance are required for teachers to use digital writing assessment tools effectively?